دور الاستدلال بالسبر و التقسيم في تعليمية النحو العربي - العربي, ركي (جامعة الوادي - University of Eloued, 2022)
ملخص: ما يزال الباحثون في حقل التعليمية يوجهون جهودهم للبحث عن أنجع الطرائق لتعليم النحو العربي، فالطرائق التي وضعت لتعليم النحو العربي قديما و حديثا نجحت على المستوى النظري، أما على المستوى التطبيقي والتجريبي فإن البون بين التنظير و التطبيق يجعلنا نعيد النظر في تلك الطرائق و البحث عن أخرى، فالنحو العربي حين وضع وضع بصحبة العلة، فمدار إثبات الحقائق في الأذهان أيا كانت على العلة، فالأدلة النقلية والعقلية غير كافية لإثبات قضية أو نفيها، و بما أن السبر والتقسيم من مسالك العلة، فهي من جهة أخرى مهارة عقلية و طريقة لتعليم النحو. الكلمات المفتاحية: السبر؛ التقسيم؛ الاستدلال؛ الدليل؛ طرائق؛ مسلك. Abstract: Researchers in the field of Didactics are still directing their efforts to search for the most effective methods for teaching Arabic grammar. The methods that were developed to teach Arabic grammar in the past and recently have succeeded on the theoretical level, but on the practical and experimental level, the disconnect between theorizing and application makes us reconsider these methods and search for In other words, the Arabic grammar is when it is placed in the company of the illness, so the extent to which the facts are proven in the minds, whatever they are on the cause, the transitional and mental evidence is insufficient to prove or deny an issue, and since sounding and partiton of vowel paths, on the other hand, is a mental skill and a way to teach grammar. key words: sounding; Partition; Inference; Guide; Methods; Course
مقال
Keywords: : sounding; Partition; Inference; Guide; Methods; Course; االسبر؛ التقسيم؛ الاستدلال؛ الدليل؛ طرائق؛ مس